The role of the erythrocyte and subsequent ATP release in blood flow and oxygen delivery to the human forearm during hypoxic exercise - Mossing, Allison Marie, author; Dinenno, Frank, advisor; Chicco, Adam, committee member; Gentile, Chris, committee member (Colorado State University. Libraries, 2014)
Hypoxia and exercise each cause ATP to be released from the erythrocyte, increasing vasodilation to match the blood flow and oxygen demands of the exercising skeletal muscle tissue (Bergfeld & Forrester, 1992; Ellsworth, 2004; Gonzalez-Alonso, Olsen, & Saltin, 2002). However, few studies have examined the extent to which ATP can be released from the erythrocyte, especially due to hypoxic exercise. We hypothesized that hypoxic exercise would cause further augmentation in erythrocyte-derived ATP release, vasodilation, and blood flow. To test this hypothesis, in 10 healthy young adults, blood samples were taken from a deep venous catheter inserted into the experimental arm and analyzed to determine and compare the amount of ATP released under normoxic and then hypoxic exercise. Forearm blood flow (FBF; Doppler ultrasound) and vascular conductance (FVC) responses to submaximal rhythmic forearm handgrip exercise (15% maximal voluntary contraction) in normoxia and during systemic hypoxia (80% arterial oxygen saturation; pulse oximetry) were measured and calculated, respectively. Compared to normoxic rest, 3 minutes of normoxic exercise significantly increased plasma ATP (45±4 nmol/L vs 101±22 nmol/L; P<0.05). Plasma ATP with hypoxic exercise was only significantly greater than normoxic rest at 30 seconds (114±4 nmol/L; P<0.05) and 3 minutes (84±12 nmol/L; P<0.05) of exercise. ATP collected at any time point with 3 minutes of hypoxic exercise was not significantly greater than with 3 minutes of normoxic exercise (P=NS). Forearm blood flow 3 minutes of hypoxic exercise (250±26 ml min-1; P<0.05) were both greater than with normoxic exercise (201±21 ml min-1; P<0.05) or normoxic rest (29±4 ml min-1; P<0.05). Forearm vascular conductance was greater with hypoxic exercise (257±29 ml min1 (100mmHg) -1; P<0.05) than with normoxic exercise (212±23 ml min-1(100mmHg) -1; P<0.05) or normoxic rest (33±4 ml min-1(100mmHg) -1; P<0.05). As plasma ATP did not continually increase with hypoxic exercise, we conclude that hypoxic exercise may not be a strong enough stimulus for erythrocyte-derived ATP release. Despite a lack in ATP release, FBF and FVC were still maintained, suggesting that ATP may not be as important for vasodilation, enhanced blood flow, and oxygen delivery to the skeletal muscle as previously thought. Other factors involved in vasodilation and blood flow augmentation during hypoxic exercise warrant further investigation.